Gambaran Pengetahuan Ibu Hamil dengan Kehamilan Risiko Tinggi di Puskesmas Gosoma Tobelo - Jumriani Jumriani; Putri Yayu (Jurnal Sehat Mandiri, 2025)
Indonesia in 2015, showed that the maternal mortality rate increased to 359 per 100,000 and Hypertension in pregnancy has an increasing proportion or scope, more than 25% of maternal deaths are caused by hypertension in pregnancy. Therefore, the government has made every breakthrough to reduce the maternal mortality rate caused by hypertension in pregnancy by increasing the role of midwives. Purpose of the Study To Find Out For A Description of the Knowledge of Pregnant Women With High-Risk Pregnancy at the Gosoma Tobelo Health Center in 2024. This type of research is Descriptive research, This research was conducted at the Gosoma Tobelo Health Center in August - September 2024, the sample in this study was 30 pregnant women. The results of the study showed that out of 30 respondents (100%), there were 12 pregnant women (40%) who had good knowledge about high-risk pregnancy, 10 pregnant women (33%) who had sufficient knowledge about high-risk pregnancy and there were 8 pregnant women (27%) who had less knowledge about high-risk pregnancy. Conclusion: Most pregnant women have good knowledge about high-risk pregnancies.